Design, Implementation, and Evaluation of Physicians Empowerment Course for Evidence-Based MRI Prescription at Bushehr University of Medical Sciences in 2021 - Soleiman Ahmady; Hedayat Salari; Atefeh Esfandiari; Reza Nemati; Amin Habibi (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: Evidence-based medicine is considered as a new and reliable approach which has new discussions on judgment to find the best evidence or qualitative evidence. This study was designed in Bushehr province for designing, implementing, and evaluating physician empowerment courses in evidence-based MRI prescriptions in the training hospitals of Bushehr University of Medical Sciences in 2021. Methods: The present study was an educational scholarship which was conducted in Bushehr province. This study was performed in two phases in accordance with Glassic criteria. A number of five workshops were designed and conducted by researchers using the ADDIE Model in systemic educational design. The course was designed through the review of texts and interviews with experts and in-depth group discussions (FGD) with the presence of seven experts. After that, this training course was evaluated and the end-of-course test was performed using the Kirkpatrick model. In order to evaluate the reaction of participants during the training course, a questionnaire was designed and its face validity and content validity were approved by experts. In addition, a four-choice test was designed based on the presented scientific content to evaluate the learning level of participants. A number of 40 questions were designed for five workshops. Descriptive statistics (frequency, mean) were used in SPSS22 for data analysis. Results: In terms of gender, 53.7 % were male and 46.3 % were female. In terms of age, 24.4 % were in the age group of 31-35 years. In terms of improving awareness, 34.1 % of participants were at a very good level after the empowerment course. Learning findings indicated that 85.7 % of participants in the final test received a passing score while 14.3 % failed. Conclusion: In general, the findings of the study indicated that holding an empowerment course for physicians in Bushehr improved their awareness and knowledge. In fact, such improvement in awareness and knowledge can reduce unnecessary prescriptions and treatment costs but improve the quality of services.